2019
DOI: 10.1016/j.celrep.2019.02.087
|View full text |Cite
|
Sign up to set email alerts
|

Nemo-like Kinase Drives Foxp3 Stability and Is Critical for Maintenance of Immune Tolerance by Regulatory T Cells

Abstract: Summary The Foxp3 transcription factor is a crucial determinant of both regulatory T (T REG ) cell development and their functional maintenance. Appropriate modulation of tolerogenic immune responses therefore requires the tight regulation of Foxp3 transcriptional output, and this involves both transcriptional and post-translational regulation. Here, we show that during T cell activation, phosphorylation of Foxp3 in T REG cells can be regulated by a TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…The other types of phosphorylation and acetylation can stabilize Foxp3 protein. Nemo‐like kinase (NLK) phosphorylates Foxp3, and prevents Stub1 from interacting with and ubiquitinating Foxp3 . Fleskens et al .…”
Section: Roles Of Foxp3 Post‐translational Modifications In the Activmentioning
confidence: 99%
See 1 more Smart Citation
“…The other types of phosphorylation and acetylation can stabilize Foxp3 protein. Nemo‐like kinase (NLK) phosphorylates Foxp3, and prevents Stub1 from interacting with and ubiquitinating Foxp3 . Fleskens et al .…”
Section: Roles Of Foxp3 Post‐translational Modifications In the Activmentioning
confidence: 99%
“…Nemo‐like kinase (NLK) phosphorylates Foxp3, and prevents Stub1 from interacting with and ubiquitinating Foxp3 . Fleskens et al . showed that TCR and costimulatory signals induce Foxp3 phosphorylation through the activation of NLK in a TGF‐β‐activated kinase 1 (TAK1)‐dependent manner.…”
Section: Roles Of Foxp3 Post‐translational Modifications In the Activmentioning
confidence: 99%
“…The function of Sirt1 is regulated by the mammalian sterile 20-like kinase (Mst)1, which increases Foxp3 acetylation and promotes its activity both indirectly, by inhibiting the activity of Sirt1, and directly, by interacting with Foxp3 and preventing its binding to Sirt1 (139). As Foxp3 is also regulated through phosphorylation of specific sites and, depending on the phosphorylation site, it can be either activated or inhibited (143,144). A novel TCR-mediated mechanism regulating Foxp3 phosphorylation involves the activation of the Nemo-like kinase (NLK), a serine/threonine protein kinase involved in regulation of cell proliferation and apoptosis (144).…”
Section: Post-translational Modification Network Regulating Foxp3mentioning
confidence: 99%
“…As Foxp3 is also regulated through phosphorylation of specific sites and, depending on the phosphorylation site, it can be either activated or inhibited (143,144). A novel TCR-mediated mechanism regulating Foxp3 phosphorylation involves the activation of the Nemo-like kinase (NLK), a serine/threonine protein kinase involved in regulation of cell proliferation and apoptosis (144). During T cell activation, TGF-β activates NLK that, in turn, binds and phosphorylates Foxp3 on multiple residues, inducing its deubiquitination and inhibiting the proteasomal degradation [ Figure 2; (144)].…”
Section: Post-translational Modification Network Regulating Foxp3mentioning
confidence: 99%
“…However, Nemo-like kinase (NLK) is considered a mitogen-activated, serine-threonine-protein kinase, a Wnt/βcatenin signaling inhibitor; NLK protein coding gene significantly downregulated various inflammatory-mediated transcription factors including transforming growth factor beta and nuclear factor-κB. Some studies have shown NLK protein critically regulated T cell-mediated immunological reaction, apoptosis, and inflammation via activation of Wnt/β-catenin molecular mechanisms [14,15]. Moreover, recent studies established that Wnt signaling pathways are not only implicated in cardiac cell development, proliferation, and differentiation but also significantly engaged in the pathological process of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%